Comparison on seaweed communities of the two rocky shores in Sarawak, Malaysia. - S. , C. Wong; Zakaria @ Ya, Muta Harah; Bujang, Japar Sidik; Arshad, Aziz (2012)
A study on seaweeds was carried out at Tanjung (Tg.) Batu (3°12’28.3”N, 113°02’38.4”E) and Kampung (Kg.) Kuala Nyalau (3°37’50.8”N, 113°22’16.1”E), Bintulu, Malaysia, from January to October 2008. This study examined the diversity and monthly distribution of seaweeds at two rocky shores with distinct landform characteristics and differences in their environmental conditions. A total of 32 seaweeds were identified belonging to 20 families and 27 genera comprising of 28 species (9 Chlorophyta, 5 Phaeophyta and 14 Rhodophyta) at Kg. Kuala Nyalau and 15 species (5 Chlorophyta, 2 Phaeophyta and 8 Rhodophyta) at Tg. Batu. Rhodophyta was dominant at both sites. Based on Bray-Curtis similarity evaluation, four distinct clusters on species occurrence in relation to months were observed at Tg. Batu: I–January, February and March, II–June and July, III–April and August, IV–September and October and, three clusters at Kg. Kuala Nyalau: I–February, March and April, II–January, III–June, July, August, September and October. Besides the topography and wave physical forces, a combination of some environmental (physical and chemical) factors were influencing the occurrence and differences in seaweed communities between the sites.